Memorial de formação: narrativas de uma estudante de Educação do Campo - VITORIANO, Aline Luzia Barbosa Pereira (2024)
This work presents the journey of the author, a student of the Countryside Education Course, based on her training memorial, which, mobilized by social movements in defense of human rights, reflects on her experiences throughout her life and training, as well such as the contributions of the Rural Education Course in teacher training and social leadership. With the perspective of narrative research, the objective was to highlight the intertwining between the different phases of his life and training based on remembrance. The dialogues with Paulo Freire, Carlos Rodrigues Brandão, Jorge Larrosa Michael Connelly, Jean Clandinin, Guilherme Prado, Inês Bragança, contributed to weaving knowledge that brings the theme of experiences throughout the phases of life and training, both through memories and through language. Regarding the methodological approach, in dialogue with narrative research in the educational field, the research raises issues of teacher training and social leadership, organized into thematic axes. The path taken in research and training enabled some lessons, among them, discovering herself as a teacher-narrator, the expansion and power of authorial writing, defender of human rights, leadership training in its political and social dimensions